Predictors Influencing the Choice of Master’s Programs in the Tourism Industry - RAKHIMBERDINOVA, Madina; NUREKENOVA, Elvira; DUARTE, Ángel; SUIEUBAYEVA, Saltanat; ORDABAYEVA, Mainur (Journal of Environmental Management and Tourism, 2022)
The authors analyzed trends in integration of education, science and business in an industrially developed area. New ways of interaction between universities, research organizations and businesses are proposed especially in the field of tourism industry. The dynamic change in global economic processes entails reform education in this area of study, which from a method of simple reproduction of labor was transformed into a source of growth for economically and socially active population groups capable of acting in a competitive environment. The need to train highly qualified personnel to quickly changing working conditions is a priority for states and organizations, focused on meeting their economic goals. In Kazakhstan, the requirements for university education are increasing. It due to both new conditions on the labor market and the increased role of “lifelong education". The number of people applying for university education is growing. Is growingcompetition between different universities, between universities and other research institutions, between private and public education. Representatives of the business community, in turn, make demands on how they would like to see graduates of Kazakh universities. Business success depends on the ability of employees of firms to quickly restructure their activities in the changing conditions. That is why domestic business is becoming interested in the reform education: it needs specific specialists definitely in tourism area, and it is ready to financially support their training.